Asset Allocation and Risk Assessment in the Securities Portfolio Management System - L. I. Yuzvovich; M. I. Lvova (Финансы: теория и практика, 2025)
The agro-industrial complex is an important component of the economy. However, this sector is characterized by a complex structure, limited resources and dependence on government actions. For these reasons, portfolio management in the agro-industrial sector requires special attention when developing the investment strategy. In this regard, the study of the strategy and methodology of managing the securities portfolio of the agro-industrial complex is an urgent topic in the context of restructuring of the Russian economy. The main task in managing the securities portfolio is to attract the financial resources of the company for the needs of organizations and to increase their economic activities. Investment portfolio in the market of financial instruments is an independent product, its implementation in full or in part brings profit to the investor when he makes investments of monetary resources on the stock exchange. As a rule, the securities market implements an asset portfolio with established proportions of profitability and risk, the indicators of which may improve or worsen during the management process. As part of structural asset allocation development and  risk assessment, the authors set out to explore various approaches to developing mechanisms for managing securities portfolio in the agro-industrial sector in order to maximize profits for the investor. The subject of the study is approaches to managing securities portfolio in the agro-industrial sector, data analysis methods used in conducting the study, as well as possible investment strategies in this sector. The methodological basis of this work is the economic and statistical methods of information processing, as well as mathematical modeling. Based on the data obtained, it is concluded that new data in the field of securities portfolio management in the agro-industrial sector allow investors to make optimal and profitable decisions when choosing investment strategies based on a risk-based approach. As a result, the current state of the agro-industrial complex was studied and the risks of the securities portfolio of the agro-industrial complex of Russia were assessed, recommendations for the formation of a securities portfolio in the agro-industrial sector for the future were developed.